2021
DOI: 10.1002/jnm.2908
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of Z‐shaped gate dielectric modulated (DM) tunnel field‐effect transistor‐(TFET) based biosensor with extended horizontal N+ pocket

Abstract: In this paper, a Z‐shaped gate dielectric modulated (DM) tunnel field‐effect transistor‐(TFET) based biosensor with extended horizontal n+ pocket in the source region is proposed and different performances were investigated. Effective structural modification has been done by considering the filed induced quantum confinements effects to enhance the various performances of the device in terms of ON current (Ion) and threshold voltage. The horizontal pocket beneath the source region of the ZHP‐DM‐TFET biosensor e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…5a, we observed that even the dielectric constant value is doubled, it shows a little variation in the ambipolar current, which is neglected and treated as constant. This is due to the effect of the energy band profile modulation (BPM), where the further widening of the bandgap is not possible because of the limitation on the minimum doping profile of the drain [27][28][29][30][31]. Even the surrounded gate structure shows high controllability over the channel, but the technique overlapping gate-on-drain depends on drain doping concentration.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…5a, we observed that even the dielectric constant value is doubled, it shows a little variation in the ambipolar current, which is neglected and treated as constant. This is due to the effect of the energy band profile modulation (BPM), where the further widening of the bandgap is not possible because of the limitation on the minimum doping profile of the drain [27][28][29][30][31]. Even the surrounded gate structure shows high controllability over the channel, but the technique overlapping gate-on-drain depends on drain doping concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Even the surrounded gate structure shows high controllability over the channel, but the technique overlapping gate-on-drain depends on drain doping concentration. Here, we considered the drain doping of 5 × 10 18 , which cannot further reduce due to the sensor's construction constraints [27][28][29][30][31]. Figure 5b represents the potential variation of the GAA-TFET biosensor for different dielectric constant values of the biomolecules.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Separate Cosine Transfigure (DCT) and Multi-Scale Transform are often utilised transforms for image emulsion (MST). Deep literacy (DL) has recently flourished in a number of image processing and computer vision operations [7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%